Prevalence of Rheumatic Heart Disease in Mathagadi Village Development Committee of Palpa District - Bhattarai, Anil; Shrestha, Bibhush; Devbhandari, Ruchi; Tripathee, Sabin (Journal of National Heart and Lung Society Nepal, 2022)
Introduction: Cardiovascular diseases are the leading cause of morbidity and mortality worldwide. There is increasing burden of these diseases especially when it comes to a developing country like Nepal. The survey was done to determine the prevalence of Rheumatic heart disease and its burden. Methods: A Community based cross sectional study was done as a part of a demographic survey conducted among the residents of Mathagadi VDC of Palpa district. Cardiac auscultation and transthoracic echocardiography were performed. Abnormal findings on auscultation (murmurs, abnormal heart sounds) were further evaluated with the help of screening echocardiography by Cardiologist. Results: Out of total 2795 people screened, 37 individuals were found to have RHD, confirmed with a 2D echocardiographic findings. Mitral regurgitation was found to be the predominant lesion with 13 cases. Conclusion: The study revealed a large of proportion of cardiovascular diseases in Mathagadi VDC. It became clear that due to lack of proper health services, a large of number of cases may be either undiagnosed or under treated.